Psikoedukasi Sebagai Prevensi Perilaku Seksual Pranikah Remaja Putra Yang Tinggal Di Panti Asuhan - Yuliana Susanti; Setia Asyanti (JIP (Jurnal Intervensi Psikologi), 2022)
Teenagers living in orphanages have limited parental assistance during their sexual development, putting them at risk of premarital sexual behavior. Psychoeducation, which involves providing information and training skills, has been widely known as a psychological intervention but has not been widely used to address sexual behavioural problems in adolescents. The purpose of this study is to find out if interventions in the form of psychoeducation can reduce premarital sexual behavior in young men living in orphanages. The research method uses quasi-experimentation with one group pretest-posttes design. Research subjects numbered 6 people selected using purposive sampling with the criteria of adolescents aged 15-19 years, living in the orphanage X Boyolali, conducting premarital sexual behavior. The research instruments used a scale of sexual behavior with data analysis using the Wilcoxon test. The results of this study showed that psychoeducation is effective for lowering premarital sexual behavior in adolescents